Age-dependent chromosomal distribution of male-biased genes in Drosophila - Zhang, Yong E.; Vibranovski, Maria D.; Krinsky, Benjamin H.; Long, Manyuan (Genome Research, 2010)
We investigated the correlation between the chromosomal location and age distribution of new male-biased genes formed by duplications via DNA intermediates (DNA-level) or by de novo origination in Drosophila. Our genome-wide analysis revealed an excess of young X-linked male-biased genes. The proportion of X-linked male-biased genes then diminishes through time, leading to an autosomal excess of male-biased genes. The switch between X-linked and autosomal enrichment of male-biased genes was also present in the distribution of both protein-coding genes on the D. pseudoobscura neo-X chromosome and microRNA genes of D. melanogaster. These observations revealed that the evolution of male-biased genes is more complicated than the previously detected one-step X→A gene traffic and the enrichment of the male-biased genes on autosomes. The pattern we detected suggests that the interaction of various evolutionary forces such as the meiotic sex chromosome inactivation (MSCI), faster-X effect, and sexual antagonism in the male germline might have shaped the chromosomal distribution of male-biased genes on different evolutionary time scales.
10.1101/gr.107334.110